Measuring Digital Maturity in Local Government: A Case Study of Karanganyar Regency Technological Adoption and Organizational Readiness - Huda, Muhammad Nurul; Putra, Romi Iriandi; Akbar, Paisal (ARISTO, 2025)
Although there is no fixed definition for digital maturity, it can be concluded that digital maturity refers to the ability of an organization to use digital technology effectively and efficiently in achieving its strategic goals. This research proposes a new framework to assess the digital maturity of local governments called the Digital Maturity Model for Local Governments in Indonesia (DMM-LGI). The framework has two main dimensions, namely technology adoption and organizational readiness. This research method uses a mixed approach, combining quantitative and qualitative research methods. The research process begins with a literature review from scopus-indexed journals, followed by the formulation of a digital maturity framework, measuring the level of digital maturity, identifying a certain level, and providing recommendations for further digital transformation. The results showed that the digital maturity of the local government of Karanganyar regency was at the level of average digitalization, where the main obstacle was that there were limitations in aspects of adequate and quality human resources (HR). In addition, the excessive number of applications and information systems poses new problems, especially related to integration and interoperability. The suggestion for future research is that the concept of digital maturity is dynamic, nothing is fixed and will continue to evolve as science and technology advance